Remote Smart Switch - Mohd Radhi, Nawwal; Abdullah, Raihana; Roslan, Sharifah Azzila; Yusop, Azli (Multidisciplinary Applied Research and Innovation, 2022)
In this paper Smart Switch project will be discussed and explained in detail. Smart Switch used Internet of Things based (IoT) system and used Blynk to connect the software and the hardware. Significantly, Smart Switch lets the consumer to control the condition of fan and lamp switches remotely without manually pressed the conventional switch on the wall. Electrical consumer tend to forget to turn off their electrical appliance switches specifically the fan and the lamp which will lead to waste of electrical consumption in their household. The Smart Switch’s main objective is to prevent electrical waste and facilitate controlling the switches of the lamp and fan remotely wherever the consumer is. In addition, Smart Switch can track the condition of the switches either is still turn on or off. It allows the consumer not in the particular connection range to have access to deal with the switch. Smartphones and electrical appliances in the home need to be connected to Wi-Fi. Therefore, the user can control the lights and a fan via a smartphone without using conventional wall switches. Methodologies used such as flowcharts and coding also explained in detail to design the operation of our Smart Switch project. The development of our hardware such as the microcontroller, DC motor and other electronic components to build our prototype are decided followed by testing and calibrating our project. As a consequence, the result and discussion can obtain from the testing and calibrating of the circuit. This project, for example, explained the capabilities of the Blynk and the extent to which programming can assist us. It helps us understand how the Internet of Things (IoT) works in this modern era, where smartphone is a device we always have with us.